Crescimento, comércio, instituições e geografia: novas evidências empíricas - Fabris, Thiago Rocha (Universidade do Vale do Rio dos Sinos, 2021)
The thesis main objective is to measure the impacts of trade, institutions, and geography on economic growth. For this, two approaches were used. In the first, a bibliometric study was conducted referring to the literature that specifically addresses this topic. The focus was to identify the empirical models that minimize endogeneity problems during the period that includes trade policies related to import substitution, export promotion, and trade opening. The second approach used econometric models to measure the effects of trade, institutions, and geography on economic growth in a sample of 133 countries in the period 1996-2014. The proposed model is based on the studies by Frankel and Romer (1999), Rodrik et al. (2004), Santos Silva and Tenreyo (2006), and Squalli and Wilson (2011). The results, related to bibliometric analysis, identified 62 studies according to the criteria established by the research. The parameters estimated in the econometric models suggest that trade, institutions, and geography contribute to explain the countries' per capita income. Trade had the highest coefficients, suggesting that trade transactions between countries would be the main profound determinant of economic growth. The impacts of trade, institutions, and geography appear to be less pronounced in low-income countries, especially in parameters that reflect institutions' influence on per capita income.
Keywords: Crescimento; Comércio; Instituições; Geografia; Endogenia; Growth; Trade; Institutions; Geography; Endogeny; ACCNPQ::Ciências Sociais Aplicadas::Economia